Revisiting the ideological negotiation of Indonesian identity, 1900–1942 - Yuliantri, Rhoma Dwi Aria (Politics, religion & ideology, 2024)
This paper examines the discourses on Indonesian identity as they were negotiated by Indonesian intellectuals in the late colonial period, 1900–1942. During this period, ethnic diversity and Islamism constituted key issues in which different intellectuals exchanged their thoughts as to what it meant to be an Indonesian. This paper argues that, while various ideological discourses for the formation of Indonesian national identity had developed in the early twentieth century, the depth that these discourses were debated and agreed upon by the Indonesian intellectual elite was asymetrical. Strong nationalist discourses had promoted a key political instrument by which to unite a people of diverse ethnicity, race, and religion. On the other hand, the debates on the discourse of Islamic identity during the same period lacked consensus among Muslim scholars and between Islamists and secular nationalists, especially concerning the concept of unity, nationalism, and independence, and the role of women and polygamy. Notwithstanding this, Javanese Islamic syncretism and the colonial containment policy towards Islam also contributed as external factors which served to constrain Islamists from positing an overt Islamic identity. Concurrently, it raised the nationalists’ racial transcendence as a shared value of being Indonesian.